Effects of 10-week soccer training program on anthropometric, psychological, technical skills and specific performance parameters in youth soccer players - Miranda, R. E. E. P. C.; Antunes, H. K. M.; Pauli, J. R.; Puggina, E. F.; da Silva, A. S. R. (Science & Sports, 2013)
Objectives: To verify the influence of 10-week soccer training program on anthropometric, psychological, technical skills and specific performance parameters in youth players. Equipment and methods: Thirteen young athletes were evaluated two times along the experiment (i.e. in T1, and T2). On the first day, anthropometric evaluation, sexual maturity status, flexibility and psychological parameters were assessed. On the second day, soccer technique tests were performed with 30 min of passive recovery in between. On the third day, the sprint tests (i.e. 10, 20 and 50 m) were measured. Finally, the lactate minimum test was performed on the fourth day. Results: Independently from sexual maturity status changes, a 10-week soccer training program with similar characteristics of volume and intensity may lead to significant changes (P = 0.05) in the body mass, body mass index, lean body mass, total mood disturbance, flexibility, slalom dribble and lob pass tests, 30- and 50-m time-trial performances, running intensity at the lactate minimum test and anaerobic parameters of the Running Anaerobic Sprint Test (RAST). In conclusion, based on the importance of soccer technique tests to talent identification, soccer coaches should use this type of evaluation during training routine.